Archeology as a Metaphor in Contemporary Culture - Woźny, Jacek (Qualitative Sociology Review, 2021)
The scientific discipline of archeology has gone through various stages of its development and improvement of research methods. First, it was combined with ancient history and the history of art. In the mid-nineteenth century, the base of its chronology was on biblical events. Modernist archeology of the twentieth century focused on classifying monuments and reconstructing cultural processes. In the second half of the twentieth century, archeology inspired other disciplines of culture and science to “stratigraphically” look at their own history. In this way, the stratification of scientific thought (archeology of knowledge), the history of photography (archeology of photography), and the media (archeology of media) began to be analyzed. Archeology has become a cognitive metaphor in contemporary culture. Lack of knowledge of the theoretical and methodological achievements worked out by archaeologists may, after some time, lead to the trivialization and petrification of the archaeological metaphor, although today it still seems fresh and innovative for “archeology of media,” “archeology of photography,” or “archeology of modernism.”